TRANSVITAL MEANING IN THE LATE AGE - Akopian , L.S. (Modern Psychology, 2019)
The article reviews the concept of a semantic trans vital of an individual in older age. The increase in human life span in all countries is not only a social but also a psychological problem. There are serious reasons to revise the established views on both age periodization, and the inner world of an old man. The system of conceptual categories of the national psychology raises the necessity to amplify the concepts of "leading activity" and "psychological growths». Trans vital meaning in the system of semantic formations of late-life personality is characterized by the search for new meanings motivating social or other activity in the final stage of life and the realization of post life continuation in certain personal achievements: leave good memories, ideas in generated tangible and intangible values, in offspring. The feeling of being wanted, being a part of a family, inner circle, a sense of self-worth to the community allows a person to adapt at this age stage. A distinctive feature of late-life individuals is awareness of the possibility of the virtual continuation of life in one or another form of micro- and macro group memory. Search for trans vital sense as going beyond the individual human life in the final stage may be a problem of the semantic integrational design of life path of man. The meaning of life is the special value for the later age of a person.